Effects of Therapies Involving Plyometric-Jump Training on Physical Fitness of Youth with Cerebral Palsy: A Systematic Review with Meta-Analysis - Exal Garcia-Carrillo; Rodrigo Ramirez-Campillo; Mikel Izquierdo; Ragab K. Elnaggar; José Afonso; Luis Peñailillo; Rodrigo Araneda; Daniela Ebner-Karestinos; Urs Granacher (MDPI AG, 2024)
The aim of this systematic review was to assess the effects of plyometric-jump training (PJT) on the physical fitness of youth with cerebral palsy (CP) compared with controls (i.e., standard therapy). The PRISMA 2020 guidelines were followed. Eligibility was assessed using the PICOS approach. Literature searches were conducted using the PubMed, Web of Science, and SCOPUS databases. Methodological study quality was assessed using the PEDro scale. Data were meta-analyzed by applying a random-effects model to calculate Hedges' g effect sizes (ES), along with 95% confidence intervals (95% CI). The impact of heterogeneity was assessed (I2 statistic), and the certainty of evidence was determined using the GRADE approach. Eight randomized-controlled studies with low-to-moderate methodological quality were included, involving male (n = 225) and female (n = 138) youth aged 9.5 to 14.6 years. PJT interventions lasted between 8 and 12 weeks with 2-4 weekly sessions. Compared with controls, PJT improved the muscle strength (ES = 0.66 [moderate], 95% CI = 0.36-0.96, p < 0.001, I2 = 5.4%), static (ES = 0.69 [moderate], 95% CI= 0.33-1.04, p < 0.001, I2 = 0.0%) and dynamic balance (ES = 0.85 [moderate], 95% CI = 0.12-1.58, p = 0.023, I2 = 81.6%) of youth with CP. Therefore, PJT improves muscle strength and static and dynamic balance in youth with CP compared with controls. However, more high-quality randomized-controlled trials with larger sample sizes are needed to provide a more definitive recommendation regarding the use and safety of PJT to improve measures of physical fitness.